Influence of carbon and nitrogen sources on growth, sporulation and aggressiveness of three seed-borne fungi in pigeonpea - K.V.R.V. VARMA, ALAKA PANDE and (Indian Phytopathology, 2012)
Aggressiveness of three seed-borne fungi from two vars. of pigeonpea was influenced by nutrients in the media during the growth phase; disaeeharides and ammonium salts induced more growth and higher aggressiveness in Alternaria alternata but not in Drechslera hawaiiensis. Cladosporium cladosporioides was not much influenced by type of nitrogenous source. Overall, growth response in liquid media and aggressiveness on host were parallel.